From oral charms to written heritage: Four Yezidi prayer-incantations from Sinjar, Iraq - Spät, Eszter (Bulletin of the School of Oriental and African Studies, 2025)
Early researchers of Yezidis, a small religious minority of the Middle East, often noted with dismay that Yezidis did not say or know prayers. This observation is partially supported by modern-day research, as knowledge of orally transmitted religious texts and their performance is mostly limited to people recognized as religious experts. However, there exists a special sub-genre of prayers which are known and recited by "ordinary"Yezidis. Although they are referred to as "prayers"(dua), these texts do not constitute part of formal religious performances during ceremonial occasions. They could better be described as verbal charms or incantations aimed at healing sickness or warding off evil. This article gives a translation of four previously unrecorded such "prayers", describes their role in oral tradition, and finally shows how they are now being transformed from performed (and practical) oral religion to written heritage by the younger generation.
Created from Fastlane, Scopus look-up
Keywords: Cultural heritage; Religious minorities of Iraq; Religious orality; Scripturalization; Yezidis